THE COST BARRIER OF CONSUMERS CLASS ACTION IN INDONESIA AND HOW TO LEARN FROM THERE THE PROCEDURE HAS BEEN ADOPTED - Elisabeth Sundari (European Scientific Journal, ESJ, 2013)
Indonesia’s consumer law protection has adopted class action procedure as a strategic response to consumers’ access to justice in the 1990s. When it was applied in some consumer cases in Indonesia, most of them failed with the cost barrier to notify all class members as the main factor.Based on Watson point of view of divergent element in the comparative law study, this article first, examines the difficulties facing those who commencing consumers’ class action in Indonesia. Second, looks to Australian procedural law and practices to explore whether similar problems exist. Third, make use of it comparatively to overcome the cost barrier in Indonesia.Looking at some Australian provisions and practices, and with respect to the Indonesian situation, it analized that the solution to the cost barrier in consumers’ class actions for Indonesian litigants may be expressed in the terms of:1. Optimizing the principles of having ‘the judges involved’ and ‘the efficiency of justice’ to arrange the most efficient way of notifying all group members;2. Supporting the growth of commercial litigation funders based on rules;3. Establishing a funding support body, like, the class action funding support agency by the Government,The two main litigation funders, the commercial funder and the class action funding support agency, then may work in harmony. Where a class action lawsuit cannot be supported financially by the commercial funder, it may be supported by the class action funding support agency.